2020
DOI: 10.21203/rs.2.20438/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative study between Fenton and Intergrowth 21 charts in a sample of Lebanese premature babies

Abstract: Background: Different charts are used to assess premature growth. The Fenton chart, based on prenatal growth, was used in in the intensive care unit of the Notre Dame des Secours University Hospital to assess premature newborns’ development. Intergrowth21 is a new multidisciplinary, multiethnic growth chart better adapted to premature growth. Our objective was to compare both charts Fenton and Intergrowth21 in order to implement Intergrowth in our unit.Methods: We analyzed 318 files of premature babies born wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…While for extremely low birth weight infants, Intergrowth 21st Project growth standards have been shown to be superior to Fenton Growth Charts [ 13 ], the picture for moderate to late term infants is not so clear. A recent study, where more than 50% of infants were between 34 and 36 weeks of gestation, showed that for the 2-week period immediately following birth, Fenton growth charts were superior to Intergrowth 21st [ 14 ]. Of particular concern is that Intergrowth-21st charts underestimate the rate of SGA compared to Fenton charts, which is of relevance in a lower socioeconomic community such as is the case with our study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…While for extremely low birth weight infants, Intergrowth 21st Project growth standards have been shown to be superior to Fenton Growth Charts [ 13 ], the picture for moderate to late term infants is not so clear. A recent study, where more than 50% of infants were between 34 and 36 weeks of gestation, showed that for the 2-week period immediately following birth, Fenton growth charts were superior to Intergrowth 21st [ 14 ]. Of particular concern is that Intergrowth-21st charts underestimate the rate of SGA compared to Fenton charts, which is of relevance in a lower socioeconomic community such as is the case with our study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…To date, there are still few studies that have compared different population growth charts with Intergrowth-21st. 2,5,6,[17][18][19][20][21][22][23] However, its ability to identify the SGA infants remains under debate. 11 The aim of the present study is to compare Fenton, Olsen, and Intergrowth-21st growth charts, regarding the classification at birth and incidence of SGA in very preterm infants.…”
mentioning
confidence: 99%